The Moderating Role of Childhood Experiences in the Relationship between Personality Traits and Social Anxiety (Studia Doctoralia Psychology and Educational Science, 2024)
This study aims at investigating the relationship between childhood experiences, social anxiety, and personality factors. The sample consisted of 121 participants aged between 18 and 71 years (M = 28.54, SD = 13.12). Of these, 78.5% (N = 95) are female, and 20.7% (N = 25) male, one person identified as genderfluid, also 51.2% (N = 62) come from the urban area and 48.8% (N = 59) from the rural area. Following the analysis of the statistical data, it was observed that positive relationships with the family significantly influence the levels of social anxiety in the different age categories, and agreeableness moderates the relationship between positive relationships with the family in the age range of 5-12 years and performance anxiety. In conclusion, analysis of these results may bring a deeper understanding of the interactions between positive family relationships, social anxiety/performance anxiety, and other influencing factors, contributing to the development of more effective and personalized interventions in the treatment of social anxiety.